Analysis of the UI/UX of the Skylar Topup Website Information System Using the Usability Scale (SUS) System Method - Ronaldo Julian PK; Karnadi; Zulhipni Reno Saputra Elsi (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Technological developments in the field of information systems have brought significant changes in the way we conduct transactions, communicate, and access services. One of the aspects that is focused on in the development of a website-based information system is the design of the user interface (UI) and user experience (UX). With technological advancements and wider adoption, intuitive, accessible, and user-friendly UI/UX design has become essential to ensure that information systems can meet users' needs efficiently and effectively. This study aims to evaluate user experience focusing on the ease of use and effectiveness of the user interface (UI) on the SkylarTopup information system. This process involves identifying challenges faced by users in interacting with the website, such as difficulties in navigation, slow response times, and design aspects that can be improved. Through SUS-based analysis, it is hoped that recommendations can be generated to improve the quality of UI/UX, so that SkylarTopup's information system can be more optimal, efficient, and better meet user needs. The results of the SUS score obtained show that although this system can be used quite well, there is potential for a significant improvement in terms of usability.